Sudan civil service: one century of development - Eissa, Garoot Suleiman (2014)
This proposed paper seeks to outline the general growth of the Sudan Civil Service throughout the Twentieth Century. However, the primary focus is on the period following independence. The basic contention is that such growth was primarily in response to political demands which came either in the form of public demands for government services, the need to spearhead economic and social developmentor expectations and demands of the incumbent government reflecting its political goals and ideologies. Three remarkable phases can be identified: first the colonial phase where civil service growth could be explained in terms of goals of the colonial administration which included establishment of law and order, provision of a minimum of services and economic growth of certain sectors of importance for the colonial centre. The second phase was the period after independence and up to the 1990s. This was characterized by rapid growth of the public sector in response to demands of economic and social development on the one hand and prevalence of socialist ideology for two decades on the other; resulting in a strategy of development centering on the public sector at the expense of the private sector. Predictably, such a strategy retarded economic growth, thus leading to the third and current phase. The third phase was inspired by regime change bringing to power an anti-socialist Islamic government and a general international orientation towards redefinition of the role of the public sector in development. The most notable outcomes were: privatization, streamlining of the civil service and new managerialism. Descriptive historical qualitative methodology based on secondary sources will be utilised.